Th17 cell plasticity towards a T-bet-dependent Th1 phenotype is required for bacterial control in Staphylococcus aureus infection. - Patricia Bartsch; Christoph Kilian; Malte Hellmig; Hans-Joachim Paust; Alina Borchers; Amirrtavarshni Sivayoganathan; Leon Enk; Yu Zhao; Nikhat Shaikh; Henning Büttner; Milagros N Wong; Victor G Puelles; et al. (PLoS Pathogens, 2022)
Staphylococcus aureus is frequently detected in patients with sepsis and thus represents a major health burden worldwide. CD4+ T helper cells are involved in the immune response to S. aureus by supporting antibody production and phagocytosis. In particular, Th1 and Th17 cells secreting IFN-γ and IL-17A, are involved in the control of systemic S. aureus infections in humans and mice. To investigate the role of T cells in severe S. aureus infections, we established a mouse sepsis model in which the kidney was identified to be the organ with the highest bacterial load and abundance of Th17 cells. In this model, IL-17A but not IFN-γ was required for bacterial control. Using Il17aCre × R26YFP mice we could show that Th17 fate cells produce Th17 and Th1 cytokines, indicating a high degree of Th17 cell plasticity. Single cell RNA-sequencing of renal Th17 fate cells uncovered their heterogeneity and identified a cluster with a Th1 expression profile within the Th17 cell population, which was absent in mice with T-bet/Tbx21-deficiency in Th17 cells (Il17aCre x R26eYFP x Tbx21-flox). Blocking Th17 to Th1 transdifferentiation in Th17 fate cells in these mice resulted in increased S. aureus tissue loads. In summary, we highlight the impact of Th17 cells in controlling systemic S. aureus infections and show that T-bet expression by Th17 cells is required for bacterial clearance. While targeting the Th17 cell immune response is an important therapeutic option in autoimmunity, silencing Th17 cells might have detrimental effects in bacterial infections.